Some children with autism have latent social skills that can be tested - Hrdlicka M (Dove Medical Press, 2017)
Michal Hrdlicka,1 Tomas Urbanek,2 Maria Vacova,1 Stepanka Beranova,1 Iva Dudova1 1Department of Child Psychiatry, Charles University Second Faculty of Medicine and University Hospital Motol, Prague, 2Institute of Psychology, Academy of Sciences, Brno, Czech Republic Background: The idea of latent social skills in autism emerged as a possible interpretation of the rapid (but temporary) improvement of autistic subjects in oxytocin studies. We tested a hypothesis that a normal response to Item No 59 “Secure Base” from the third version of the Autism Diagnostic Interview – Revised (ADIR-59) could indicate the presence of latent social skills in autism.Methods: We examined 110 autistic children (88 boys and 22 girls) with a mean age of 6.0±2.5 years (range: 2.2–14.8 years) using the Autism Diagnostic Observation Schedule (ADOS) – Generic. A diagnosis of mental retardation was established in 68 autistic children (62%).Results: The difference in the ADOS social domain between children aged ≤5 years on one side and children older than 5 years on the other side was significant in subjects with normal responses to ADIR-59 (9.60 vs 6.47; P=0.031) but not in those with abnormal responses to ADIR-59 (10.62 vs 9.63; P=0.537). In a predictive model, lower ADOS social domain scores were predicted by older age (P=0.001), lower scores on the ADIR-59 (P=0.01), and the absence of mental retardation (P=0.049).Conclusion: The results support the hypothesis that the normal response to item ADIR-59 “Secure Base” indicates the presence of latent social skills in autism that might foretell further social growth in older autistic subjects. Keywords: autism, latent social skills, Autism Diagnostic Interview – Revised, Autism Diagnostic Observation Schedule, prediction